Femoral Tunnel Positioning in Anterior Cruciate Ligament Reconstruction: Anteromedial Portal versus Transtibial Technique—A Randomized Clinical Trial - Venosa, Michele; Delcogliano, Marco; Padua, Roberto; Alviti, Federica; Delcogliano, Antonio (Joints, 2017)
Purpose The purpose of this study was to investigate, through three-dimensional computed tomography (3D-CT), the accuracy of femoral tunnel positioning in patients undergoing anterior cruciate ligament (ACL) reconstruction, comparing transtibial (TT) and anteromedial (AM) techniques.Methods We evaluated postoperative 3D-CT scans of 26 patients treated with ACL reconstruction with hamstrings autograft using a low accessory AM portal technique and 26 treated with the TT technique. The position of the femoral tunnel center was measured with the quadrant method.Results Using quadrant method on CT scans, femoral tunnels were measured at a mean of 32.2 and 28.1% from the proximal condylar surface (parallel to Blumensaat line) and at a mean of 31.2 and 15.1% from the notch roof (perpendicular to Blumensaat line) for the AM and TT techniques, respectively.Conclusion The AM portal technique provides more anatomical graft placement than TT techniques.Level of Evidence Level I, randomized clinical study.
Keywords: anterior cruciate ligament; reconstruction; femoral tunnel; anteromedial portal; transtibial; computed tomography